2010
DOI: 10.1371/journal.pcbi.1000644
|View full text |Cite
|
Sign up to set email alerts
|

SnugDock: Paratope Structural Optimization during Antibody-Antigen Docking Compensates for Errors in Antibody Homology Models

Abstract: High resolution structures of antibody-antigen complexes are useful for analyzing the binding interface and to make rational choices for antibody engineering. When a crystallographic structure of a complex is unavailable, the structure must be predicted using computational tools. In this work, we illustrate a novel approach, named SnugDock, to predict high-resolution antibody-antigen complex structures by simultaneously structurally optimizing the antibody-antigen rigid-body positions, the relative orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
166
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(167 citation statements)
references
References 56 publications
(84 reference statements)
1
166
0
Order By: Relevance
“…Following computer modeling of the 72A1 antibody variable-region peptide sequences, in silico identification of the gp350/ 220 interaction with the 72A1 antibody was performed by spatially aligning the 72A1 variable-region peptide sequences with the amino-terminal portion of gp350 using the SnugDock algorithm (13). The SnugDock molecular docking program predicts the optimal alignment for close coupling of the 72A1 variable region with the gp350 molecule by identifying the lowest-energy structure between two molecules and lists the interfacing residues and types of interactions (24). The SnugDock alignment indicated that the gp350 amino terminus couples to the 72A1 variable region through four gp350 interfacing peptide sequences, namely, 14 281 .…”
Section: Resultsmentioning
confidence: 99%
“…Following computer modeling of the 72A1 antibody variable-region peptide sequences, in silico identification of the gp350/ 220 interaction with the 72A1 antibody was performed by spatially aligning the 72A1 variable-region peptide sequences with the amino-terminal portion of gp350 using the SnugDock algorithm (13). The SnugDock molecular docking program predicts the optimal alignment for close coupling of the 72A1 variable region with the gp350 molecule by identifying the lowest-energy structure between two molecules and lists the interfacing residues and types of interactions (24). The SnugDock alignment indicated that the gp350 amino terminus couples to the 72A1 variable region through four gp350 interfacing peptide sequences, namely, 14 281 .…”
Section: Resultsmentioning
confidence: 99%
“…The Rosetta SnugDock algorithm leverages the information about the flexible and/or uncertain regions of the antibody to perform robust Ab–Ag docking 8 . SnugDock simulates the induced-fit mechanism through simultaneous optimization of several degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the existence of conformational changes in the Ag binding site has been widely recognized, their role in the adaptive immune system has not been structurally elucidated. Furthermore, understanding these conformational changes should help to improve Ab modeling, docking, and engineering (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%